Excitation of arbitrary irregular waveguide with an inhomogeneous anisotropic dielectric filling - A. A. Kurayev; T. L. Popkova; A. O. Rak (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
A general form of the equation excitation arbitrary irregular waveguide with an inhomogeneous anisotropic dielectric filling is formulated.